Implementasi Program Pemberdayaan Usaha Mikro Batik Dalam Lingkup Klaster Batik Kota Semarang - Purnanto, Cahyo Uji; Suryaningsih, Margaretha; Kismartini, Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
A cluster of batik is an association of micro, small and medium enterprises batik, the problems of the same kind that has formed by a city government semarang through the agency of planning and development of the city of semarang.Then the government of semarang giving authority to the department of cooperatives, micro business small and medium enterprises, the city of semarang to do program msmb, in accordance with the articles which are handed down by the city of semarang budget. The process of the implementation of umkm, cluster batik is good because it has in accordance with act number 20 year 2008 and the result of the implementation of umkm, cluster batik not good because there are several factors impediment to implementation of that are not routine, as control a cluster of batik's human resources dominated by the old people, facilities and infrastructure to inadequate.Then, during a function of the research the researchers found another phenomenon affecting the implementation of empowerment namely a communication that is not so good.In addition, there is a factor supporting the implementation of empowerment namely contribution, our commitment readiness, competence, financial institutions dept. of cooperatives, director of semarang city and umkm, social relationships and the degree of engagement a member of a cluster of have been good.